Comparing Fire Behaviour of Restrained Cold‐Formed Steel Columns with Stiffened and Unstiffened Sections. Issue 2 (1st September 2021) - Laím, Luís; Craveiro, Helder D.; Simões, Rui
Abstract: Although, some experimental investigations have already been conducted and reported in the literature on cold‐formed steel columns under fire conditions, tests on the structural response of CFS columns in compression with intermediate and edge stiffeners and with restrained thermal elongation are rarely found in the literature, hence the relevance of the current investigation. In the present study, the effect of i) cross‐section shape (including single and built‐up sections), ii) web and edge stiffener configurations (webs with and without intermediate stiffeners and flanges with single edge fold stiffeners and double edge fold stiffeners), iii) slenderness (columns with different boundary conditions: pinned and fixed ends), and iv) stiffness of the surrounding structure to the thermal elongation of such columns have been investigated using an experimental campaign. Based on the research results it is clear that the overlapping regions, composite action, number of stiffeners, section geometry and load level take a crucial role in the fire structural behavior of CFS columns.